Optical transparent self-cleaning coating composition and preparation method thereof
The self-cleaning coating composition, using a mixed matrix with nanocellulose and titanium dioxide, enhances anti-aging and self-cleaning abilities, ensuring effective removal of organic dirt and maintaining transparency.
Patent Information
- Application Number
- CN202411399272.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2024-12-20
AI Technical Summary
Existing self-cleaning coatings lose their cleaning ability due to stubborn stains and surface aging, lacking effective anti-aging properties.
A composition comprising a mixed matrix of waterborne polyurethane, polylactic acid, polydimethylsiloxane, and epoxy fatty acid, reinforced with nanocellulose and titanium dioxide nanoparticles, and enhanced with hydrophobic and anti-UV additives, which improves transparency, adhesion, and self-cleaning performance.
The coating exhibits improved mechanical strength, weather resistance, and extended self-cleaning performance through photocatalytic degradation of organic dirt, maintaining high light transmittance and low volatile organic compounds.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of self-cleaning coatings, and in particular to an optically transparent self-cleaning coating composition and a preparation method thereof. Background Art
[0002] Self-cleaning coatings can cause surface pollutants or dust particles to automatically fall off under the influence of external forces such as gravity, rain, and wind, or be removed through photocatalytic degradation. They have the advantages of saving water, energy, and environmental protection, and have important application prospects in industries such as construction, transportation, and new energy.
[0003] In recent years, it has become a research hotspot for advanced functional coatings. According to different self-cleaning principles, self-cleaning coatings can be divided into two categories: super hydrophobic and super hydrophilic. They both achieve their own self-cleaning effect through the action of water. The above self-cleaning coatings cannot effectively maintain their own cleaning ability after stubborn adhesion of large stains or surface aging. Based on the above statement, the present application provides an optically transparent self-cleaning coating composition and a preparation method thereof. Summary of the invention
[0004] The purpose of the present application is to improve the anti-aging ability and self-cleaning ability of an optically transparent self-cleaning coating composition, and to provide an optically transparent self-cleaning coating composition and a preparation method thereof compared to the prior art.
[0005] In a first aspect, the present application provides an optically transparent self-cleaning coating composition, comprising the following raw materials in parts by weight: 60-95 parts of a mixed matrix, 15-25 parts of a composite photocatalyst, 1-5 parts of a hydrophobic additive, 1-5 parts of an enhancer, 5-15 parts of a bio-based solvent, and 1-3 parts of an anti-ultraviolet additive; The mixed matrix is prepared by the following method: The aqueous polyurethane, polylactic acid, polydimethylsiloxane, polyamide and epoxy fatty acid are weighed in a mass ratio of 25-40:20-30:4-10:1:1 and set aside for later use; the weighed aqueous polyurethane is put into a high shear mixer, and deionized water and ethanol are added in a mass ratio of 2-4:5-8 for stirring until the aqueous polyurethane is completely dissolved; the weighed polylactic acid, polydimethylsiloxane, polyamide and epoxy fatty acid are crushed into powder and gradually added into the aqueous polyurethane for continuous stirring at a stirring speed of 1000-1300 r / min; after a mixture is formed, an ultrasonic oscillator is used to homogenize the mixture, and then the mixture is transferred to a vacuum environment for degassing treatment to obtain a mixed matrix.
[0006] Preferably, the reinforcing agent comprises nanocellulose and titanium dioxide nanoparticles in a mass ratio of 7-10:2.
[0007] By adopting the above technical scheme, the present application selects waterborne polyurethane, polylactic acid, polydimethylsiloxane, polyamide and epoxy fatty acid as the mixed matrix of the coating. By adding polydimethylsiloxane, the coating can have good transparency, water resistance and weather resistance. By adding polyamide and epoxy fatty acid, the coating can have good adhesion and weather resistance. By adding a hydrophobic additive, the hydrophilicity and self-cleaning properties of the coating can be improved. At the same time, the reinforcing agent prepared from nanocellulose and titanium dioxide nanoparticles improves the mechanical strength and wear resistance of the coating on the one hand, and on the other hand, utilizes titanium dioxide nanoparticles to produce hydroxyl radicals under light to decompose organic dirt. Combined with the addition of anti-UV additives, it can further enhance the weather resistance of the coating and extend the life cycle of the coating, effectively improving the self-cleaning performance of the coating.
[0008] Preferably, the nanocellulose is prepared by the following method: a. Remove the stems and leaves of the collected cassia and jute and leave the roots, wash, dry and dry them; b. Soak the dried cassia and jute roots in 42-45% hydrochloric acid at a temperature of 60-65°C for 6-12 hours to hydrolyze and decompose the macromolecular cellulose into nanocellulose; c. neutralizing the hydrochloric acid in the nanocellulose with 0.5-2 mol / L alkaline water, and then repeatedly washing with deionized water to remove residual hydrochloric acid; d. The washed nanocellulose is vacuum dried to obtain the desired nanocellulose.
[0009] Preferably, the mass ratio of cassia to jute is 4:3, and the mass ratio of lactic acid, polyacrylic acid and dichloromethane is 1:0.1-0.2:0.2-0.5.
[0010] Preferably, the vacuum drying temperature is 50-70° C., and the drying time is 2-3 hours.
[0011] Preferably, the composite photocatalyst is prepared by compounding modified strontium titanate and nitrogen-doped titanium dioxide in a mass ratio of 1:0.5-0.9, the hydrophobic additive is prepared by compounding polyfluoroolefin and polyvinyl alcohol in a mass ratio of 1:1-1.5, and the bio-based solvent is butyl acetate.
[0012] In a second aspect, the present application provides a method for preparing an optically transparent self-cleaning coating composition, comprising the following preparation steps: S1. Weigh the raw material mixed matrix, composite photocatalyst, hydrophobic additive, reinforcing agent, bio-based solvent and anti-ultraviolet additive by weight for later use; S2, mixing the mixed matrix with the bio-based solvent, stirring evenly to ensure full dissolution, and obtaining a mixed solution A; S3, adding the reinforcing agent, the hydrophobic additive, the anti-ultraviolet additive and the composite photocatalyst to the mixed solution A in sequence, stirring evenly to ensure full dissolution, and obtaining a mixed solution B; S4, mixing the mixed solution B, leaving it to stand and removing bubbles, to obtain the desired optically transparent self-cleaning coating composition.
[0013] Compared with the prior art, the advantages of the present application are: the present application uses a mixture of water-based polyurethane, polylactic acid, polydimethylsiloxane, polyamide and epoxy fatty acid as the mixed matrix of the coating. By adding polydimethylsiloxane, the coating can have good transparency, water resistance and weather resistance. By adding polyamide and epoxy fatty acid, the coating can have good adhesion and weather resistance. By adding hydrophobic additives, the hydrophilicity and self-cleaning properties of the coating can be improved. At the same time, the enhancer prepared from nanocellulose and titanium dioxide nanoparticles improves the mechanical strength and wear resistance of the coating on the one hand, and on the other hand, titanium dioxide nanoparticles are used to generate hydroxyl radicals under light to decompose organic dirt. At the same time, combined with the addition of anti-ultraviolet additives, the weather resistance of the coating can be further enhanced and the life cycle of the coating can be extended, effectively improving the self-cleaning performance of the coating. DETAILED DESCRIPTION
[0014] The present application is further described in detail below with reference to the embodiments.
[0015] Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without making any creative work shall fall within the scope of protection of this application.
[0016] Embodiment 1: The present invention provides an optically transparent self-cleaning coating composition, comprising the following raw materials in parts by weight: 60 parts of a mixed matrix, 15 parts of a composite photocatalyst, 1 part of a hydrophobic additive, 1 part of a reinforcing agent, 5 parts of a bio-based solvent, and 1 part of an anti-ultraviolet additive; The composite photocatalyst is prepared by compounding modified strontium titanate and nitrogen-doped titanium dioxide in a mass ratio of 1:0.5, the hydrophobic additive is prepared by compounding polyfluoroolefin and polyvinyl alcohol in a mass ratio of 1:1, and the bio-based solvent is butyl acetate.
[0017] The mixed matrix is prepared by the following method: Aqueous polyurethane, polylactic acid, polydimethylsiloxane, polyamide and epoxy fatty acid are weighed in a mass ratio of 25:20:4:1:1 and set aside for later use. The weighed aqueous polyurethane is put into a high shear mixer, and deionized water and ethanol are added in a mass ratio of 2:5 for stirring until the aqueous polyurethane is completely dissolved. The weighed polylactic acid, polydimethylsiloxane, polyamide and epoxy fatty acid are crushed into powder and gradually added into the aqueous polyurethane and continuously stirred at a stirring speed of 1000 r / min. After the mixture is formed, an ultrasonic oscillator is used to homogenize the mixture, and then it is transferred to a vacuum environment for degassing to obtain a mixed matrix.
[0018] The reinforcing agent includes nanocellulose and titanium dioxide nanoparticles in a mass ratio of 7:2.
[0019] Furthermore, in this embodiment, nanocellulose is prepared by the following method: a. Remove the stems and leaves of the collected cassia and jute and leave the roots, wash, dry and dry them; b. Soak the dried cassia and jute roots in 42% hydrochloric acid at a temperature of 60-65°C for 6 hours to hydrolyze and decompose the macromolecular cellulose into nanocellulose; c. neutralizing the hydrochloric acid in the nanocellulose with 0.5 mol / L alkaline water, and then repeatedly washing with deionized water to remove residual hydrochloric acid; d. The washed nanocellulose is vacuum dried to obtain the desired nanocellulose.
[0020] Among them, the mass ratio of cassia to jute is 4:3, the mass ratio of lactic acid, polyacrylic acid and dichloromethane is 1:0.1:0.2, the vacuum drying temperature is 50°C, and the drying time is 2h.
[0021] A method for preparing an optically transparent self-cleaning coating composition comprises the following preparation steps: S1. Weigh the raw material mixed matrix, composite photocatalyst, hydrophobic additive, reinforcing agent, bio-based solvent and anti-ultraviolet additive by weight for later use; S2, mixing the mixed matrix with the bio-based solvent, stirring evenly to ensure full dissolution, and obtaining a mixed solution A; S3, adding the reinforcing agent, the hydrophobic additive, the anti-ultraviolet additive and the composite photocatalyst to the mixed solution A in sequence, stirring evenly to ensure full dissolution, and obtaining a mixed solution B; S4, mixing the mixed solution B, leaving it to stand and removing bubbles, to obtain the desired optically transparent self-cleaning coating composition.
[0022] Embodiment 2: The present invention provides an optically transparent self-cleaning coating composition, comprising the following raw materials in parts by weight: 95 parts of a mixed matrix, 25 parts of a composite photocatalyst, 5 parts of a hydrophobic additive, 5 parts of a reinforcing agent, 15 parts of a bio-based solvent, and 3 parts of an anti-ultraviolet additive; Among them, the composite photocatalyst is compounded by modified strontium titanate and nitrogen-doped titanium dioxide in a mass ratio of 1:0.9, the hydrophobic additive is compounded by polyfluoroolefin and polyvinyl alcohol in a mass ratio of 1:1.5, and the bio-based solvent is butyl acetate.
[0023] The mixed matrix is prepared by the following method: The aqueous polyurethane, polylactic acid, polydimethylsiloxane, polyamide and epoxy fatty acid are weighed in a mass ratio of 40:30:10:1:1 and set aside for later use. The weighed aqueous polyurethane is put into a high shear mixer, and deionized water and ethanol are added in a mass ratio of 4:8 for stirring until the aqueous polyurethane is completely dissolved. The weighed polylactic acid, polydimethylsiloxane, polyamide and epoxy fatty acid are crushed into powder and gradually added into the aqueous polyurethane and continuously stirred at a stirring speed of 1300 r / min. After the mixture is formed, an ultrasonic oscillator is used to homogenize the mixture, and then it is transferred to a vacuum environment for degassing treatment to obtain a mixed matrix.
[0024] The reinforcing agent includes nanocellulose and titanium dioxide nanoparticles in a mass ratio of 10:2.
[0025] Furthermore, in this embodiment, nanocellulose is prepared by the following method: a. Remove the stems and leaves of the collected cassia and jute and leave the roots, wash, dry and dry them; b. Soak the dried cassia and jute roots in 45% hydrochloric acid at a temperature of 65°C for 12 hours to hydrolyze and decompose the macromolecular cellulose into nanocellulose; c. neutralizing the hydrochloric acid in the nanocellulose with 2 mol / L alkaline water, and then repeatedly washing with deionized water to remove residual hydrochloric acid; d. The washed nanocellulose is vacuum dried to obtain the desired nanocellulose.
[0026] Among them, the mass ratio of cassia to jute is 4:3, the mass ratio of lactic acid, polyacrylic acid and dichloromethane is 1:0.2:0.5, the vacuum drying temperature is 70°C, and the drying time is 3h.
[0027] A method for preparing an optically transparent self-cleaning coating composition comprises the following preparation steps: S1. Weigh the raw material mixed matrix, composite photocatalyst, hydrophobic additive, reinforcing agent, bio-based solvent and anti-ultraviolet additive by weight for later use; S2, mixing the mixed matrix with the bio-based solvent, stirring evenly to ensure full dissolution, and obtaining a mixed solution A; S3, adding the reinforcing agent, the hydrophobic additive, the anti-ultraviolet additive and the composite photocatalyst to the mixed solution A in sequence, stirring evenly to ensure full dissolution, and obtaining a mixed solution B; S4, mixing the mixed solution B, leaving it to stand and removing bubbles, to obtain the desired optically transparent self-cleaning coating composition.
[0028] Embodiment 3: The present invention provides an optically transparent self-cleaning coating composition, comprising the following raw materials in parts by weight: 80 parts of a mixed matrix, 20 parts of a composite photocatalyst, 4 parts of a hydrophobic additive, 4 parts of a reinforcing agent, 10 parts of a bio-based solvent, and 2 parts of an anti-ultraviolet additive; Among them, the composite photocatalyst is compounded by modified strontium titanate and nitrogen-doped titanium dioxide in a mass ratio of 1:0.5, the hydrophobic additive is compounded by polyfluoroolefin and polyvinyl alcohol in a mass ratio of 1:1.2, and the bio-based solvent is butyl acetate.
[0029] The mixed matrix is prepared by the following method: Aqueous polyurethane, polylactic acid, polydimethylsiloxane, polyamide and epoxy fatty acid are weighed in a mass ratio of 30:25:6:1:1 and set aside for later use. The weighed aqueous polyurethane is put into a high shear mixer, and deionized water and ethanol are added in a mass ratio of 3:4 for stirring until the aqueous polyurethane is completely dissolved. The weighed polylactic acid, polydimethylsiloxane, polyamide and epoxy fatty acid are crushed into powder and gradually added into the aqueous polyurethane and continuously stirred at a stirring speed of 1200 r / min. After the mixture is formed, an ultrasonic oscillator is used to homogenize the mixture, and then it is transferred to a vacuum environment for degassing treatment to obtain a mixed matrix.
[0030] The reinforcing agent includes nanocellulose and titanium dioxide nanoparticles in a mass ratio of 7:2.
[0031] Furthermore, in this embodiment, nanocellulose is prepared by the following method: a. Remove the stems and leaves of the collected cassia and jute and leave the roots, wash, dry and dry them; b. Soak the dried cassia and jute roots in 43% hydrochloric acid at a temperature of 62°C for 9 hours to perform a hydrolysis reaction to decompose the macromolecular cellulose into nanocellulose; c. neutralizing the hydrochloric acid in the nanocellulose with 1 mol / L alkaline water, and then repeatedly washing with deionized water to remove residual hydrochloric acid; d. The washed nanocellulose is vacuum dried to obtain the desired nanocellulose.
[0032] Among them, the mass ratio of cassia to jute is 4:3, the mass ratio of lactic acid, polyacrylic acid and dichloromethane is 1:0.15:0.3, the vacuum drying temperature is 60°C, and the drying time is 2.5h.
[0033] A method for preparing an optically transparent self-cleaning coating composition comprises the following preparation steps: S1. Weigh the raw material mixed matrix, composite photocatalyst, hydrophobic additive, reinforcing agent, bio-based solvent and anti-ultraviolet additive by weight for later use; S2, mixing the mixed matrix with the bio-based solvent, stirring evenly to ensure full dissolution, and obtaining a mixed solution A; S3, adding the reinforcing agent, the hydrophobic additive, the anti-ultraviolet additive and the composite photocatalyst to the mixed solution A in sequence, stirring evenly to ensure full dissolution, and obtaining a mixed solution B; S4, mixing the mixed solution B, leaving it to stand and removing bubbles, to obtain the desired optically transparent self-cleaning coating composition.
[0034] In order to verify the comprehensive performance of the weather-resistant and waterproof photocurable coatings prepared in Examples 1-3 of the present application, the applicant set up Comparative Examples 1-2, which are as follows: Comparative Example 1: The present invention provides an optically transparent self-cleaning coating composition, comprising the following raw materials in parts by weight: 60 parts of a mixed matrix, 15 parts of a composite photocatalyst, 1 part of a hydrophobic additive, 1 part of a reinforcing agent, 5 parts of a bio-based solvent, and 1 part of an anti-ultraviolet additive; The composite photocatalyst is prepared by compounding modified strontium titanate and nitrogen-doped titanium dioxide in a mass ratio of 1:0.5, the hydrophobic additive is prepared by compounding polyfluoroolefin and polyvinyl alcohol in a mass ratio of 1:1, and the bio-based solvent is butyl acetate.
[0035] The mixing base is water-based polyurethane.
[0036] The reinforcing agent includes nanocellulose and titanium dioxide nanoparticles in a mass ratio of 7:2.
[0037] Furthermore, in this embodiment, nanocellulose is prepared by the following method: a. Remove the stems and leaves of the collected cassia and jute and leave the roots, wash, dry and dry them; b. Soak the dried cassia and jute roots in 42% hydrochloric acid at a temperature of 60-65°C for 6 hours to hydrolyze and decompose the macromolecular cellulose into nanocellulose; c. neutralizing the hydrochloric acid in the nanocellulose with 0.5 mol / L alkaline water, and then repeatedly washing with deionized water to remove residual hydrochloric acid; d. The washed nanocellulose is vacuum dried to obtain the desired nanocellulose.
[0038] Among them, the mass ratio of cassia to jute is 4:3, the mass ratio of lactic acid, polyacrylic acid and dichloromethane is 1:0.1:0.2, the vacuum drying temperature is 50°C, and the drying time is 2h.
[0039] A method for preparing an optically transparent self-cleaning coating composition comprises the following preparation steps: S1. Weigh the raw material mixed matrix, composite photocatalyst, hydrophobic additive, reinforcing agent, bio-based solvent and anti-ultraviolet additive by weight for later use; S2, mixing the mixed matrix with the bio-based solvent, stirring evenly to ensure full dissolution, and obtaining a mixed solution A; S3, adding the reinforcing agent, the hydrophobic additive, the anti-ultraviolet additive and the composite photocatalyst to the mixed solution A in sequence, stirring evenly to ensure full dissolution, and obtaining a mixed solution B; S4, mixing the mixed solution B, leaving it to stand and removing bubbles, to obtain the desired optically transparent self-cleaning coating composition.
[0040] Comparative Example 2: The present invention provides an optically transparent self-cleaning coating composition, comprising the following raw materials in parts by weight: 60 parts of a mixed matrix, 15 parts of a composite photocatalyst, 1 part of a hydrophobic additive, 1 part of a reinforcing agent, 5 parts of a bio-based solvent, and 1 part of an anti-ultraviolet additive; The composite photocatalyst is prepared by compounding modified strontium titanate and nitrogen-doped titanium dioxide in a mass ratio of 1:0.5, the hydrophobic additive is prepared by compounding polyfluoroolefin and polyvinyl alcohol in a mass ratio of 1:1, and the bio-based solvent is butyl acetate.
[0041] The mixed matrix is prepared by the following method: Aqueous polyurethane, polylactic acid, polydimethylsiloxane, polyamide and epoxy fatty acid are weighed in a mass ratio of 25:20:4:1:1 and set aside for later use. The weighed aqueous polyurethane is put into a high shear mixer, and deionized water and ethanol are added in a mass ratio of 2:5 for stirring until the aqueous polyurethane is completely dissolved. The weighed polylactic acid, polydimethylsiloxane, polyamide and epoxy fatty acid are crushed into powder and gradually added into the aqueous polyurethane and continuously stirred at a stirring speed of 1000 r / min. After the mixture is formed, an ultrasonic oscillator is used to homogenize the mixture, and then it is transferred to a vacuum environment for degassing to obtain a mixed matrix.
[0042] Among them, the reinforcing agent is titanium dioxide nanoparticles.
[0043] A method for preparing an optically transparent self-cleaning coating composition comprises the following preparation steps: S1. Weigh the raw material mixed matrix, composite photocatalyst, hydrophobic additive, reinforcing agent, bio-based solvent and anti-ultraviolet additive by weight for later use; S2, mixing the mixed matrix with the bio-based solvent, stirring evenly to ensure full dissolution, and obtaining a mixed solution A; S3, adding the reinforcing agent, the hydrophobic additive, the anti-ultraviolet additive and the composite photocatalyst to the mixed solution A in sequence, stirring evenly to ensure full dissolution, and obtaining a mixed solution B; S4, mixing the mixed solution B, leaving it to stand and removing bubbles, to obtain the desired optically transparent self-cleaning coating composition.
[0044] Performance testing: According to the test standards, the optically transparent self-cleaning coating compositions prepared in Examples 1-3 of the present application and Comparative Examples 1-2 were respectively coated on glass surfaces to prepare test samples, and the sample performances were tested after being placed in a test room at a temperature of 25° C. and a relative humidity of 55% for 2 hours.
[0045] According to GB / T 23986-2009 “Determination of Volatile Organic Compound (VOC) Content of Paints and Varnishes - Gas Chromatography”, the air quality of the sample in the indoor environment after coating was tested. The coating range of the test piece was 40cmx40cm and the coating thickness was 40nm.
[0046] According to ISO 4040 "Determination of light transmittance and reflectance of optical coatings", the light transmittance of the sample was tested. The specimen size was 40cmx40cm, the glass thickness was 0.5cm, and the coating thickness was 40nm.
[0047] According to GB / T 31815-2015 "Self-cleaning coatings for exterior surfaces of buildings", the self-cleaning rate of the test specimens was tested. The specimen specifications were 40cmx40cm, the glass thickness was 0.5cm, and the coating thickness was 40nm.
[0048] The test results are shown in Table 1 below:
[0049]
[0050] It can be seen from the data shown in Table 1 above that the optically transparent self-cleaning coating composition prepared in Examples 1-3 of the present application has high light transmittance, low organic volatiles, high self-cleaning rate and excellent comprehensive performance.
[0051] It can be seen from the data shown in Example 1 and Comparative Example 1 that Example 1 of the present application can significantly improve the self-cleaning rate of the coating by pre-preparing a mixed matrix of water-based polyurethane, polylactic acid, polydimethylsiloxane, polyamide and epoxy fatty acid, compared with directly adding the water-based polyurethane to the matrix, and the volatility of volatile organic compounds is also reduced.
[0052] It can be seen from the data shown in Example 1 and Comparative Example 2 that Example 1 of the present application can further improve the self-cleaning rate of the coating by mixing nanocellulose and titanium dioxide nanoparticles as a reinforcing agent.
[0053] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An optically transparent self-cleaning coating composition, characterized in that: The raw materials include the following parts by weight: 60-95 parts of mixed matrix, 15-25 parts of composite photocatalyst, 1-5 parts of hydrophobic additive, 1-5 parts of enhancer, 5-15 parts of bio-based solvent, and 1-3 parts of anti-ultraviolet additive; The mixed matrix is prepared by the following method: The aqueous polyurethane, polylactic acid, polydimethylsiloxane, polyamide and epoxy fatty acid are weighed in a mass ratio of 25-40:20-30:4-10:1:1 for later use; the weighed aqueous polyurethane is put into a high shear mixer, and deionized water and ethanol are added in a mass ratio of 2-4:5-8 for stirring until the aqueous polyurethane is completely dissolved; the weighed polylactic acid, polydimethylsiloxane, polyamide and epoxy fatty acid are crushed into powder and gradually added into the aqueous polyurethane for continuous stirring at a stirring speed of 1000-1300 r / min; after a mixture is formed, an ultrasonic oscillator is used to homogenize the mixture, and then the mixture is transferred to a vacuum environment for degassing treatment to obtain a mixed matrix.
2. An optically transparent self-cleaning coating composition according to claim 1, characterized in that: The reinforcing agent comprises nanocellulose and titanium dioxide nanoparticles in a ratio of 7-10:2 by mass.
3. An optically transparent self-cleaning coating composition according to claim 2, characterized in that: The nanocellulose is prepared by the following method: a. Remove the stems and leaves of the collected cassia and jute and leave the roots, wash, dry and dry them; b. Soak the dried cassia and jute roots in 42-45% hydrochloric acid at a temperature of 60-65°C for 6-12 hours to hydrolyze and decompose the macromolecular cellulose into nanocellulose; c. neutralizing the hydrochloric acid in the nanocellulose with 0.5-2 mol / L alkaline water, and then repeatedly washing with deionized water to remove residual hydrochloric acid; d. The washed nanocellulose is vacuum dried to obtain the desired nanocellulose.
4. An optically transparent self-cleaning coating composition according to claim 3, characterized in that: The mass ratio of cassia to jute is 4:3, and the mass ratio of lactic acid, polyacrylic acid and dichloromethane is 1:0.1-0.2:0.2-0.
5.
5. An optically transparent self-cleaning coating composition and a preparation method thereof according to claim 3, characterized in that: The vacuum drying temperature is 50-70° C., and the drying time is 2-3 hours.
6. An optically transparent self-cleaning coating composition according to claim 3, characterized in that: The composite photocatalyst is compounded from modified strontium titanate and nitrogen-doped titanium dioxide in a mass ratio of 1:0.5-0.9, the hydrophobic additive is compounded from polyfluoroolefin and polyvinyl alcohol in a mass ratio of 1:1-1.5, and the bio-based solvent is butyl acetate.
7. A method for preparing an optically transparent self-cleaning coating composition according to any one of claims 1 to 6, characterized in that: The method comprises the following preparation steps: S1. Weigh the raw material mixed matrix, composite photocatalyst, hydrophobic additive, reinforcing agent, bio-based solvent and anti-ultraviolet additive by weight for later use; S2, mixing the mixed matrix with the bio-based solvent, stirring evenly to ensure full dissolution, and obtaining a mixed solution A; S3, adding the reinforcing agent, the hydrophobic additive, the anti-ultraviolet additive and the composite photocatalyst to the mixed solution A in sequence, stirring evenly to ensure full dissolution, and obtaining a mixed solution B; S4, mixing the mixed solution B, leaving it to stand and removing bubbles, to obtain the desired optically transparent self-cleaning coating composition.
Citation Information
Patent Citations
Preparation method of nano TiO2 self-cleaning transparent coating
CN103102791A
Self-cleaning type coating for concrete substrates, method for preparing self-cleaning type coating and method for applying same
CN107652866A
